BUDAYA ORGANISASI DAN KEPUASAN KERJA PENGARUHNYA TERHADAP KOMITMEN ORGANISASIONAL MELALUI KEDISIPLINAN KERJA PEGAWAI YAYASAN PENDIDIKAN DULUWO LIMO LO POHALAA GORONTALO - Yakup (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
This research aims to know the influence of organizational culture and job satisfaction on organizational commitment through employee work discipline education foundation of Duluwo Limo lo Pohalaa Gorontalo. Research question: (1) Are there positive and significant influences directly organizational culture to employee organizational commitment. (2) Are there positive and significant influences directly job satisfaction on employee organizational commitment. (3) Are there positive and significant influences directly work discipline to employee organizational commitment. (4) Are there positive and significant influences directly organizational culture to employee work discipline. (5) Are there positive influences a job satisfaction to employee work discipline. (6) Are there a close relationship between an organizational culture with job satisfaction of employee. The population in the study is employees with sampling method with a selected sample of 100 people which is used as an analysis unit. Data was collected through questionnaires. Data analysis techniques were carried out by path analysis, data processing using Lisrel 8.70. Based on the test results, it found (1) there is a positive and significant influence directly organizational culture on employee organizational commitment. (2) there is a positive and significant influence directly job satisfaction on employee organizational commitment. (3) there is a positive and significant influence directly work discipline to employee organizational commitment. (4) there is a positive and significant influence directly organizational culture on employee work discipline. (5) there is a positive and significant influence directly job satisfaction on employee work discipline. (6) there is a very close relationship between organizational culture and employee job satisfaction. Research recommendations (1) Organizational culture if improved, then the employee organizational commitment will increase. (2) High job satisfaction can increase employee organizational commitment. (3) Work discipline if improved, then the employee organizational commitment will increase. (4) Organizational culture has a positive and significant effect directly to employee work discipline, if organizational culture is improved, then employee work discipline will increase. (5) Job satisfaction has a positive and significant influence directly to employee work discipline. If job satisfaction is improved, then the employee work discipline will increase. (6) organizational culture and job satisfaction have a very close relationship n increasing organizational commitment and employee work discipline, hen organizational and disciplinary commitment will increase